PENGARUH SISTEM AKUNTANSI MANAJEMEN DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJERIAL PADA PT. ADIRA DINAMIKA MULTI FINANCE TBK KANTOR CABANG JAYAPURA - M, Nurul Ilmy; Mus, Abdul Rahman; Ahmad, Hamzah (Invoice : Jurnal Ilmu Akuntansi, 2021)
author has the objective to determine the effect of management accounting system and environmental uncertainty on managerial performance on PT Adira Dinamika Multifinance Tbk Branch Office Jayapura. The hypothesis of this study is: Suspected of management accounting system and environmental uncertainty have a significant impact on the performance of managerial on On Adira Dinamika Multifinance Tbk Branch Office Jayapura.  The data required in this study is primary data in the form of respondents’ assessment of management accounting system, environmental uncertainty and performance of managerial. Data collection methods used in this study is the questionnaire as well as a literature review on the books related to the subject matter covered. Data analysis techniques used by Multiple Linear Regression Test, t test, F test, Coefficient of Determination Test.  The results of this study indicate: (1) management accounting system a positively and significantly effect on the managerial performance; and (2) environmental uncertainty a positively and significantly effect on the managerial performance.Keyword: Management Accounting System, Environmental Uncertainty and Managerial Performance